Pengaruh Ice breaking dan Reward terhadap Hasil Belajar Mahasiswa Kimia pada Mata Kuliah Kimia Dasar - Zuhrah Adminira Ruslan (Entalpi Pendidikan Kimia, 2026)
Chemistry learning in higher education often faces obstacles such as low student participation and boredom, which impact learning outcomes. This study aims to analyze the effect of the implementation of icebreaking and rewards on the learning outcomes of chemistry students in the Basic Chemistry course. The study used a quantitative method with a quasi-experimental design. The research sample was students of the Chemistry Education Study Program selected through purposive sampling and divided into experimental and control groups. Treatment was given for eight meetings in the form of the implementation of ice breaking activities and the provision of rewards as motivational reinforcement. Learning outcome data were obtained through written tests that had been tested for validity and reliability, then analyzed using inferential statistics. The results showed that the average learning outcome score of the experimental group (79.74) was higher than that of the control group (73.30). The independent t-test showed a significant difference with a value of t(33) = 4.854 and p < 0.001, and an effect size of 1.41, which is considered large. These findings indicate that the implementation of ice breaking and rewards significantly improves student learning outcomes. Thus, the integration of these two strategies can be recommended as an innovative learning alternative to create a more interactive, motivational, and effective learning environment to improve student academic achievement.